Implications in the health of workers in swine confinement buildings - effects on the respiratory system - BALKAMOS (Γ.Κ. ΜΠΑΛΚΑΜΟΣ) G. C.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; TZIKA (Ε.Δ. ΤΖΗΚΑ) E. D.; PAPAIOANNOU (Δ.Σ. ΠΑΠΑΙΩΑΝΝΟΥ) D. S.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Confinement units are commonly used all over the world to raise pigs. Despite their economic advantages, their microenvironment causes severe adverse effects on the health of farm workers. Respiratory complaints which have been associated with the exposure effects of organic dust and confinement gases on humans who have long-term employment into these settings, are reviewed. These include pulmonary function changes, airways imfiammation, mucosa irritation syndrome and organic dust toxic syndrome. Furthermore, the most important zoonoses which may provoke respiratory symptoms to the swine confinement workers are briefly reviewed. It is believed that these conditions can be prevented by improving air quality, husbandry systems and adopting hygiene measures.